2016
DOI: 10.1002/elps.201600445
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lithium and transition metals in Li1Ni1/3Co1/3Mn1/3O2 (NCM) cathode material for lithium‐ion batteries by capillary electrophoresis

Abstract: In this work, we present a novel electrophoretic method that was developed for the determination of lithium and transition metals in LiNi Co Mn O cathode material after microwave digestion. The cations in the digested LiNi Co Mn O material were separated by CE and the element content was determined by UV/Vis detection. To characterize the precision of the measurements, the RSDs and concentrations were calculated and compared to those obtained with ICP-optical emission spectrometry (ICP-OES). Furthermore, a cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…For analysis of cations in the LIB research context, Vortmann-Westhoven et al showed a capillary electrophoresis (CE) separation method with UV/vis detection for the determination of lithium and transition metals after microwave digestion [135]. They compared this developed method to results obtained with IC and inductively coupled plasma-optical emission spectroscopy (ICP-OES) and could get comparable results in terms of recovery rates and general analytical figures of merit.…”
Section: Electrode Analysismentioning
confidence: 99%
“…For analysis of cations in the LIB research context, Vortmann-Westhoven et al showed a capillary electrophoresis (CE) separation method with UV/vis detection for the determination of lithium and transition metals after microwave digestion [135]. They compared this developed method to results obtained with IC and inductively coupled plasma-optical emission spectroscopy (ICP-OES) and could get comparable results in terms of recovery rates and general analytical figures of merit.…”
Section: Electrode Analysismentioning
confidence: 99%
“…demonstrated that the choice of anode material can significantly influence the capacity retention and cycle life [39] . In case of Li metal [40] or graphite anodes, [41] operating at low potentials vs. Li|Li + , the deposited Mn II showed a strong impact on performance, whereas Li 4 Ti 5 O 12 , having a high operation potential, only showed a negligible effect on performance by Mn II deposition [39] . Additionally, Gilbert et al.…”
Section: Introductionmentioning
confidence: 99%
“…[31] In regard of Mn II deposition at the anode surface, Zhan et al demonstrated that the choice of anode material can significantly influence the capacity retention and cycle life. [39] In case of Li metal [40] or graphite anodes, [41] operating at low potentials vs. Li j Li + , the deposited Mn II showed a strong impact on performance, whereas Li 4 Ti 5 O 12 , having a high operation potential, only showed a negligible effect on performance by Mn II deposition. [39] Additionally, Gilbert et al showed that the majority of capacity loss in highvoltage LIB cells can be contributed to irreversible lithium loss in the SEI at the anode, induced by TM deposition.…”
Section: Introductionmentioning
confidence: 99%
“…14,23,[27][28][29] Although there is a sophisticated repertoire of electrochemical methods for monitoring, the need for additional analytical methods is indispensable. [30][31][32][33][34] For direct solid analysis, methods like glow discharge-mass spectrometry (GD-MS), laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS), time of ight-secondary ion mass spectrometry (TOF-SIMS) and X-ray photoelectron spectroscopy (XPS). [35][36][37][38][39][40][41][42] Due to their capabilities of directly measuring the surface components, they represent promising approaches for analyzing new materials as well as the degradation of aged cells.…”
Section: Introductionmentioning
confidence: 99%